2020
DOI: 10.33945/sami/ijabbr.2020.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Study of Changes in Activity of Wheat Antioxidant Enzymes under Stress Residue of Imazethapyr Herbicide

Abstract: In order to investigate physiological and biochemical changes of wheat under stress residue of Imazethapyr herbicide (Imazethapyr), an experiment was conducted in a completely randomized design with four replications in greenhouse conditions at university of Mohaghegh Ardebili. The treatments consisted of five dose levels of herbicide Imazethapyr (0, 0.011, 0.022, 0.033 and 0.044 micrograms of herbicide) per kilogram of soil. The analysis of variance showed that the content of the main and auxiliary pigments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…The fresh leaf samples (0.5 g) of T. aestivum cultivars were prepared and homogenized in extraction buffers as described by (Hameed et al, 2015;El-Banna andAbdelaal, 2018 andRasoul et al, 2020). Enzyme activities were expressed on a weight basis.…”
Section: Enzymes Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh leaf samples (0.5 g) of T. aestivum cultivars were prepared and homogenized in extraction buffers as described by (Hameed et al, 2015;El-Banna andAbdelaal, 2018 andRasoul et al, 2020). Enzyme activities were expressed on a weight basis.…”
Section: Enzymes Assaymentioning
confidence: 99%
“…(Aminjani and Mahdiyeh, 2013;Hanci and Cebeci, 2014) suggested that chlorophyll and carotenoid content often decrease and reduce in plants exposed to pesticides. Also, Giza 178 c.v. achieved the highest photosynthesis pigments content followed by Giza 182 c.v. which recorded the lowest value (Kattab, 2019;Rasoul et. al., 2020).…”
Section: Effect Of Some Herbicides On Chlorophyll Content In Wheat Cultivarsmentioning
confidence: 99%
“…У літературі є достатньо наукових даних, що підтверджують різносторонній вплив гербіцидів на вміст фотосинтетичних пігментів і їх роль у визначенні рівня такого впливу на продуктивність культури [3,6,15,22]. Водночас це питання залишається недостатньо вивченим і потребує подальших досліджень у конкретних ґрунтово-кліматичних умовах.…”
Section: вступunclassified
“…Незважаючи на деяку активізацію утворення і накопичення хлорофілів за дії гербіцидів, максимальні їх кількості фіксували на безгербіцидному фоні за механічного контролювання бур'янів, що, очевидно, пояснюється їх певним токсичним впливом на рослини. Такі висновки цілком узгоджуються з результатами багатьох дослідників, що вказують на достовірне зниження вмісту хлорофілів у ли-стках сої за гербіцидного впливу [15,22,25], трактуючи отримані дані гальмуванням біосинтезу пігментів та їх руйнуванням за дії окислювального стресу.…”
Section: результати досліджень та їх обговоренняunclassified
“…The possible stress caused by herbicide residues infers a reduction in physiological and biochemical properties of seeds, which can generate the production of reactive oxygen species (ROS), alteration in the production of amino acids resulting in protein damage, decrease in photosynthetic pigments, and lipid peroxidation . Under these conditions, plants contain both enzymatic and nonenzymatic defense components, which involve increased activity of enzymes such as catalase (CAT), peroxidase (POD), and polyphenoloxidase (PPO), the accumulation of osmoregulatory, and the increase of carotenoids. , …”
Section: Introductionmentioning
confidence: 99%